Blood Culture Use in the Emergency Department in Patients Hospitalized with Respiratory Symptoms Due to a Non-Pneumonia Illness - Makam, Anil N. (2014)
BACKGROUND: Guidelines and performance measures recommend obtaining blood cultures in selected patients hospitalized with community-acquired pneumonia (CAP). Due to inherent diagnostic uncertainty, there may be spillover effects of these recommendations on other conditions that resemble pneumonia. METHODS: Using data from the 2002-2010 National Hospital Ambulatory Medical Care Survey (NHAMCS), a nationally representative sample of emergency department (ED) visits in the US, we analyzed trends in obtaining cultures in patients hospitalized with respiratory symptoms due to a non-pneumonia illness using linear regression. RESULTS: The most common primary admission diagnoses for these visits included heart failure (16%), chronic obstructive pulmonary disease (13%), and chest pain (12%). The proportion of cultures collected in the ED during these visits increased from 10% (95% CI, 7%-14%) in 2002 to 20% (95% CI, 16%-26%) in 2010 (p<.001 for the trend). This represented a parallel increase compared to patients hospitalized with CAP (p=.12 for the difference in trends). CONCLUSIONS: The increase in collecting cultures in the ED in patients hospitalized with respiratory symptoms due to a non-pneumonia illness suggests an important potential unintended consequence of blood culture recommendations for CAP. More attention is needed to the judicious use of blood cultures to reduce harm and costs.